O jogo da honra: uma análise sociológica sobre a produção de sentidos morais de uma elite política no Sertão de Pernambuco (1851-1997) - Sá, Giovanni Alves Duarte de (2022)
This thesis is part of the field of sociology of morals and seeks to study the concept of honor from the universe of a political elite in the Sertão of Pernambuco. We believe that the notion of honor, as a moral economy, encompasses a complex system of values that still today serves as a symbolic link for interactions between members who share the same surname, either through the exaltation of what we call the ethos of family power, or through reconversion force that turns this pride into political-electoral capital. The notion of honor has acquired different interpretations over time, which provides the research with the study of how such transformations are absorbed between individuals of the same family symbology, while attributing meaning to the challenges of the contemporary world. We start, therefore, with the following research problem: How did the logic of honor contribute to the strengthening of relations of prestige, power and political domination maintained for more than 200 years by members of the Pereira family in Serra Talhada? The city is the birthplace of the so-called Pereiras do Pajeú, a region made up of 17 municipalities, where the Pereiras began a long trajectory of bloody wars, almost always linked to political interests aimed at combating values contrary to theirs and in search of control over the structure. of State. The research data were elaborated through different methodological phases, namely: 1) Family political genealogy; 2) Mapping of group values and emotions from memory books; 3) Interviews with family members; 4) Participant observation of the family reunion event; 5) Analysis of the group's speeches at public events, on the family's website, in statements to the press and in memoirs. The general objective of this thesis is to analyze, from a procedural perspective, the dynamics of values that guide the imagination of Pereiras do Pajeú, seeking to understand how narratives based on the notion of honor have transformed over time, forging behaviors and feelings associated with the perpetuation of family power. in Serra Talhada. The specific objectives intend to understand how a dispute of moral meanings propagated by an elite influenced a game for domination through the transformation of the city's customs; to analyze how these practices contributed to the transition from a warrior ethos to a parliamentary ethos in the group, strengthening a sense of distinction claimed by the family today; demonstrate how the power of the Pereiras do Pajeú was perpetuated through relationships of support, cronyism and political kinship for generations in Serra Talhada.